Concepts of scenario methods in improvement of an enterprise - Bielińska-Dusza, Edyta (Business, Management and Economics Engineering, 2013)
Purpose of the study, principal objectives, scope of the investigation, methods employed results and principal conclusion. Uncertainty makes both theoreticians and practicioners face new tasks to fulfil. Enterprises, in order to win the competitive struggle must constantly improve their processes and structures. On the other hand, thinking in the categories of the future becomes really difficult nowadays. This creates particularly convenient conditions to apply scenario methods. In connection with the above, the purpose of this study is to characterize the essence of scenario methods employed in enterprise development. The article addresses the issue of factors conditioning proper selection of methods in the enterprise development process, the principles of scenario planning and the opportunities to apply other techniques and methods in scenario planning.